Soil organic carbon primarily control the soil moisture characteristic during forest restoration in subtropical China - Zhao, Xinyu; Zhang, Weiqiang; Feng, Yingjie; Mo, Qifeng; Su, Yuqiao; Njoroge, Brian; Qu, Chao; Gan, Xianhua; Liu, Xiaodong (Frontiers in Ecology and Evolution, 2022)
Soil organic carbon (SOC) is a crucial component of the soil carbon pool that regulates fundamental soil properties and water status. In the global context of restoring vegetation, the soil carbon-water coupling relationship has gained attention. In particular, the regulatory mechanism of SOC on soil moisture requires further research. In this study, three typical forests in subtropical China were chosen as restoration sequences to investigate the changes in SOC and soil moisture during subtropical forest restoration and its regulation mechanisms: broadleaf-conifer mixed forest (EF), broad-leaved forest (MF), and old-growth forest (LF). The soil water content (35.71±1.52%), maximum water holding capacity (47.74±1.91%), capillary water holding capacity (43.92±1.43%), and field water holding capacity (41.07±1.65%) in LF were significantly higher than those in EF (p<0.01). As forest restoration progressed, the amount of litter returning to the soil increased gradually, and the SOC content (0–100 cm) increased from 9.51±1.42 g/kg (EF) to 15.60±2.30 g/kg (LF). The SOC storage increased from 29.49±3.59 Mg/ha to 42.62±5.78 Mg/ha. On one hand, forest restoration led to a change in SOC content, which optimizes the soil structure and enhances soil porosity (path coefficient of 0.537, p<0.01), further leading to a change in soil water content (path coefficient of 0.940, p<0.01). On the other hand, the increase in SOC influenced the change in soil nutrient content, i.e., total nitrogen and total phosphorus (path coefficient of 0.842, p<0.01). Changes in SOC and soil nutrients stimulated changes in the stoichiometric ratio, i.e., C:P and N:P (path coefficients of 0.988 and −0.968, respectively, p<0.01), and the biological activity in soil changed appropriately, which eventually led to a change in soil water content (path coefficient of −0.257, p<0.01). These results highlight the changes in SOC and SWC, as well as the mechanism of SOC controlling SWC as a result of vegetation restoration, which is of tremendous importance for advancing our understanding of the eco-hydrological process of subtropical forest restoration.